Hybrid Supercapacitor Electrode Materials via Molecular Imprinting of Nitrogenous Ligands and Iron Complexes into Carbon Support. Issue 12 (16th December 2021) - Fruehwald, Holly M.; Melino, Peter D.; Zenkina, Olena V.; Easton, E. Bradley
Abstract : Novel hybrid supercapacitor materials were made by the covalent immobilization of nitrogenous ligands onto the surface of commercial carbon support (Vulcan XC-72), then coordinated to iron. The covalent attachment of the nitrogenous ligands allows for the controlled deposition of nitrogen functionalities on the surface of the carbon. The supercapacitor tests in acidic media showed significant growth of the capacitance as a result of the nitrogenous ligands on the support. Notably, the increase of the capacitance values directly correlates with the molecular loading on the surface. Following coordination of iron to the ligands on the surface further elevated the capacitance via Faradaic reactions of the metal center. Remarkably, the overall capacitance of materials significantly increased after the course of long-term cycling tests (ca. 110% or higher). At the beginning of durability studies, a small decline in capacitance was observed, due to some extent of molecular decomposition on the surface of the electrode. However, the intense cycling further propagates a steady growth of the overall capacitance of the materials. This could be attributed to the process of polymerization of physisorbed molecules/ radicals that result in the formation of a 3D network structure that eventually boosts the overall capacitance and the charge storage of the electrode.